Metaphase Chromosome Preparation from Soybean (Glycine max) Root Tips. Issue 1 (3rd March 2017) - Findley, Seth D.; Birchler, James A.; Stacey, Gary
Abstract: This unit presents a highly reliable protocol to produce and screen metaphase chromosome spreads from root tip cell suspensions of soybean ( Glycine max ), or other legumes. The procedures represent soybean‐optimized versions of protocols developed for maize. The use of pressurized nitrous oxide to reliably generate metaphase‐arrested chromosomes is crucial to overcoming one of the challenges of working with tiny and numerous soybean chromosomes. © 2017 by John Wiley & Sons, Inc.